Resistance and sensitivity of strains of Pseudomonas Aeruginosa central university hospital, Barquisimeto. Lara state (Revista Venezolana de Salud Pública, 2018)
A descriptive study was conducted in order to establish patterns of resistance and sensitivity of seventy-five (75) Pseudomonas aeruginosa strains isolated from patients hospitalized in the Central Hospital Universitario "Dr. Antonio Maria Pineda "(HCUAMP) Barquisimeto. Lara. This bacterial species is the primary cause of nosocomial infections, their habitat is the human being and the environment, as well as survive in extreme conditions, can have a high resistance to most antibiotics marketed, the sample for the study were seventy-five (75) Pseudomonas aeruginosa strains isolated from infected patients, for the selection of antibiotics was carried out the following procedure: a) Check to three (3) experts in the field, b) a survey of seven inpatient hospital services for obtain updated information on treatment in patients infected with the bacterial species. We selected sixteen (16) antibiotics for susceptibility testing used the Kirby-Bauer technique, the control strain ATCC 27853 was used in the analysis of the antibacterial effect results in resistance patterns were: ceftazidime (83.56% ) Meropenem (64%), Cefoperazone (60.81%), Ticarcillin (58.66%), Moxifloxacin (56, oo%) Aztreonam (54.66%), amikacin (54.66%), gentamicin (53.33%), Cefepime (52%), Ofloxacin (52, oo%). In patterns Sensitivity: colistin (86.66%), piperacillin-tazobactam (70.27%), piperacillin (64.00%), Netilmicin (58.66%), imipenem (52.00%) and levofloxacin (52, 00%). Of the strains tested was observed that most are resistant to the antibiotics used, which is higher than that reported in other studies, the use of antibiotics rotary could benefit patients infected with this bacterium.
Keywords: Pseudomonas aeruginosa; patterns; resistence; sensitivity